The search for sustainable domestic financing options for sexual and reproductive health in Zimbabwe - Nyagumbo, Blessing Tafadzwa (M, 2020)
The focus of this study was to identify, assess and recommend sustainable domestic financing options for Sexual and Reproductive Health in Zimbabwe. The study tracks the various health care system funding models employed by the Government of Zimbabwe from the 1980s to date highlighting their shortcomings and ultimately justifying the need for re-thinking the financing of Sexual and Reproductive Health and the need to pursue homegrown financing options. The research makes use of qualitative research methods and data is collected through key informant interviews, focus group discussions and observations. The general realisation of this study is that foreign aid which remains the backbone bank rolling the health sector is not sustainable since donor funding has timeframes and budget caps. The findings of this study establishes that the country has to implement a basket of domestic financing strategies as part of its financing model. To ensure that the health system is robust, the study also establishes that there is a critical need of strengthening the health care system. The study's findings and discussions culminates into the development of a domestic financing model. It is anticipated that this model will re-dress over 2 decades of poor primary health care outcomes, unsound governance and lack of confidence in the public health delivery system.